Effect of spray drying and storage on the stability of bayberry polyphenols - Fang, Zhongxiang; Bhandari, B. (2011)
Bayberry juice was spray dried with maltodextrin (DE 10) as a carrier and then stored under different temperature and water activities (aw). The retention of the total phenolic content (TPC) and total anthocaynins (ACN) during the drying process were about 96% and 94%, respectively, suggesting spray drying was a satisfactory technique for drying heat sensitive polyphenols. Under an aw of 0.11-0.44, the TPC and ACN in bayberry powders decreased by about 6-8% and 7-27%, respectively, after 6 months storage at 4 °C; at 25 °C for the same storage period the decreases were between 6-9% and 9-37%, respectively, while at 40 °C the decreases were in the range 7-37% and 9-94%. The anthocyanin component was more readily degraded relative to other phenolic compounds. The results suggest that bayberry powder should be stored at less than 25 °C and aw of 0.33, on account of greater polyphenol stability under such conditions. © 2011 Elsevier Ltd. All rights reserved.